The advantages of Google Scholar Ranking - Bojadjiev, Marjan; Krliu, Venera; Pavlova, Sanja; Mileva, Ivona (International Journal of English Language Education, 2024)
The ranking of universities in the world is a crucial link when it comes to the circular process called choosing the right university for each future student. During this selection process, students consider many factors. It is these rankings that help them make in-depth analysis of what different universities and professors have to offer. The purpose of this paper is to show the benefits of academic ranking of universities, faculties, professors, and researchers, as well as to get a clear picture of the degree of citation of the professors, specifically on the Google Scholar platform, while explaining the level of the faculties and universities. The criteria according to which the ranking is made is the total number of citations of professors and researchers from the universities and faculties.